Establishment of a homologous gene silencing system and gene function verification of bulb formation in Lycoris Herb.(石蒜同源基因沉默体系构建及鳞茎发生基因功能验证) - 肖潇(XIAO Xiao); 夏宜平(XIA Yiping); 崔柳(CUI Liu); 张佳平(ZHANG Jiaping); 洪震(HONG Zhen); 任梓铭(REN Ziming) (浙江大学学报. 农业与生命科学版)
In this study, we explored the construction of a homologous gene silencing system for Lycoris insularis, which is a rich wild resource in Zhejiang Province with bulbs as explants, and through this system, the biological functions of Lycoris insularis bulb genes were verified. The 1 706 bp fragment of LiCWIN gene was cloned from the bulb by using specifically designed primers. After double enzyme digestion, the virus-induced gene silencing (VIGS) recombinant vector was constructed by connection with tobacco rattle virus (TRV) vector TRV2-GFP. After the transformation of Agrobacterium tumefaciens, the damaged and stimulated bulbs were infected with the bacterial solution. After 2 d of infection, the green fluorescence was observed in the vascular tissues of bulbs, and the expression level of LiCWIN gene was significantly decreased in the silenced group, as determined by real time fluorogenic quantitative polymerase chain reaction (qRT-PCR). After 40 d of infection, compared with the empty vector control group, the number of bulblets in LiCWIN gene silencing group decreased, and their formation was delayed. The above results showed that VIGS system successfully silenced functional genes in the bulbous tissues of Lycoris insularis and had a lasting effect on the later development of bulblets. After silencing of LiCWIN gene, the formation of bulblets was blocked. This study can lay a foundation for the study of key gene functions of Lycoris bulb formation and development. . 本研究以浙江省野生资源丰富的海滨石蒜（Lycoris insularis）为材料，构建了以鳞茎为外植体的石蒜同源基因沉默体系，并通过该体系验证了海滨石蒜鳞茎发生基因的生物功能。通过设计特异性引物，从鳞茎中克隆获得LiCWIN基因片段，全长1 706 bp；经双酶切后与烟草脆裂病毒（tobacco rattle virus, TRV）载体TRV2-GFP连接，从而构建病毒诱导的基因沉默（virus-induced gene silencing, VIGS）重组载体；转化根癌农杆菌后，用菌液侵染损伤刺激后的鳞茎块。侵染2 d后，观察到鳞茎维管组织中存在绿色荧光；实时荧光定量聚合酶链反应（real time fluorogenic quantitative polymerase chain reaction, qRT-PCR）检测发现，沉默组LiCWIN基因表达量显著降低。侵染40 d后，相较于空载体对照组，LiCWIN基因沉默组小鳞茎发生数量下降且发育迟缓。上述结果表明，VIGS体系在海滨石蒜鳞茎组织中成功沉默了功能基因，且对小鳞茎后期发育的表型产生了持续影响。特别是LiCWIN基因沉默后，小鳞茎发生受阻。本研究为石蒜鳞茎发生发育关键基因的功能研究奠定了基础。